Absorption, metabolism, distribution and faecal excretion of B-type procyanidin oligomers in mice after a single oral administration of black soybean seed coat extract. Issue 10 (28th September 2018) - Wang, Liuqing; Yamashita, Yoko; Komeda, Shingo; Saito, Akiko; Ashida, Hitoshi
Abstract : The bioavailablity of (−)-epicatechin, procyanidin B2, procyanidin C1 and cinnamtannin A2 was elucidated. Abstract : We investigated the absorption, metabolism, distribution and faecal excretion of 3 B-type procyanidin oligomers, including procyanidin B2, procyanidin C1 and cinnamtannin A2, and their monomeric unit (−)-epicatechin after a single oral administration of black soybean seed coat extract (BE) to male ICR mice at 250 mg per kg body weight. Plasma, tissues and faeces samples were collected within 24 h for the determination of (−)-epicatechin, procyandidin B2, procyanidin C1 and cinnamtannin A2 with or without β-glucuronidase and sulfatase treatment by the high-performance liquid chromatography method. A portion of the B-type procyanidin oligomers and (−)-epicatechin in BE was absorbed from the small intestine after the oral administration of BE. In the plasma, absorbed procyanidins and (−)-epicatechin existed mainly as conjugates. In the tissues, procyanidin B2, procyandin C1 and cinnamtannin A2, in addition to (−)-epicatechin distributed widely, primarily in their free forms. Their conjugation occurred mainly in the small intestine, rather than in the liver. Monomeric unit (−)-epicatechin had the highest bioavailability, followed by procyanidin B2, procyanidin C1 and cinnamtannin A2.